A CASE STUDY OF TWO PREMIERSHIP FOOTBALLERS WITH SICKLE CELL TRAIT USING NOVEL TESTS OF REDOX HOMEOSTASIS. Issue 7 (11th March 2014) - Catterson, P; Moore, B; Hodgson, A; Lewis, N; Newell, J; Charles, P
Abstract : Background: Sickle cell trait (SCT) is considered a benign heterozygous carrier state (both normal haemoglobin and abnormal HbS) compatible with elite level sport, whereas the autosomal recessive state of sickle cell disease is considered incompatible with strenuous exercise. Increased production of reactive oxygen species occurs in sickle cell disease, evident as increased pro-oxidants (FORT) and reduced anti-oxidants (FORD). This has been demonstrated using a novel point-of-care test (Gizi et al. 2011). No FORT/FORD data exist in athletes with SCT. Objective and Participants: It was hypothesized that premiership football players with SCT (n=2) would show altered redox homeostasis compared to non-SCT players (n=19). These data were compared to previously published data on patients with sickle cell disease and controls. Setting: English Premiership Football Team. Design and Arisk factor assessment: A cross sectional comparison study design was adopted, and descriptive data are reported. Resting whole blood samples were collected at pre-season and mid-season and analysed immediately for FORT and FORD values. Mean values for non-SCT players were plotted against mean SCT player values (Figure 1). Results: Figure 1 Conclusions: The 2 SCT players in this case study exhibited elevated FORT values, compared to non-SCT players, although they were not extreme outliers, perhaps because athletes are exposed to other sources of pro-oxidants such as exercise. Further research is necessary with a larger cohort in order to further establish the relationship between redox homeostasis and SCT in athletes. References: Gizi et al. (2011) Assessment of oxidative stress in patients with sickle cell disease: The glutathione system and the oxidant–antioxidant status. Blood cells, Molecules and Diseases 46, pp. 220–225.